Analysis of Gear Cogs Correction Influence with Involute Worm on Bearing Ability and Gear Longevity / M.V. Chernets, R.Ja. Jarema, Ju.M. Chernets // Problems of Tribology. – 2012. – № 1. – Р. 41-44. - Чернець, М.В.; Ярема, Р.Я.; Чернець, Ю.М. (Problems of Tribology, 2014)
The value calculation method of the influence of worm gear with involute worm meshing correction on the contact durability, wear and longevity of the worm gear teeth has been presented. The regularities of the displacement influence on the appointed contact and tribocontact parameters have been established, which are presented graphically.